Book of shadows / 1 - Tiernan, Cate (Tiernan, Cate. Sweep, 2002)
A seemingly average teenage girl named Morgan begins to experience strange powers and feelings, making her crush, Cal, a Wiccan himself, wonder if she could be a blood witch, a member of one of the Seven Great Clans.